Efforts to Improve the Science Knowledge of Early Children through the Exploration Approach of the Surrounding Environment in B 5-6 Years Old Group in TK Tumbuh Kembang Anak Makassar - Nurhidaya, Andi Rezky (EduLine: Journal of Education and Learning Innovation, 2021)
Children's scientific knowledge is still underdeveloped, this is due to several factors including the learning process is rarely done outside the classroom. Then encourage educators to develop it through the Approach method of Environmental Exploration Approach. The Environmental Exploration Approach Method is one of the methods used to develop children's science knowledge. This study aims to develop children's science knowledge through an environmental exploration approach method. This type of research is Classroom Action Research (CAR) which focuses on classroom situations. Based on the results of data analysis and discussion in cycle I and cycle II, it can be concluded that the exploration approach method for the surrounding environment can develop children's science knowledge in group B in TK Tumbuh Kembang Anak Makassar. This can be seen from the increase in children's science knowledge, students who develop very well in the first cycle with indicators that children can explore the surrounding environment reaching 27.27%, while the indicator of children being able to name the objects observed in the environment reaches 18.18%. Then in cycle II, the indicator of children being able to explore the surrounding environment reached 81.81%, while the indicator of children being able to name the objects observed in the environment reached 81.81%.